Analysis of Disaster Mitigation in Minimizing Disaster Risk in Manado City - Mursid Pangalima; Dian Ferriswara; Ulul Albab; Sri Kamariyah (Parlementer : Jurnal Studi Hukum dan Administrasi Publik, 2025)
This study examines disaster mitigation efforts in minimizing disaster risk in Manado City and identifies the key challenges as well as the strategies implemented by the Regional Disaster Management Agency (BPBD: Badan Penanggulangan Bencana Daerah). Employing a qualitative descriptive approach, data were collected through interviews, direct observations, and document analysis, with the Head of BPBD serving as the primary informant. The analysis was conducted using Miles et al.’s (2014) interactive model, which consists of data condensation, data display, and conclusion drawing, thereby ensuring systematic interpretation of findings.The results indicate that disaster mitigation efforts in Manado consist of both passive and active strategies. Passive measures include strengthening institutional frameworks, enhancing governance capacity, integrating disaster management planning into regional development programs, and advancing education and research to support long-term disaster risk reduction. In contrast, active mitigation emphasizes community-based actions, such as the installation of disaster warning signs, the provision of basic disaster training for officials and volunteers, the establishment of temporary evacuation shelters, and the implementation of both structural interventions (e.g., drainage construction, flood control) and non-structural measures (e.g., socialization, counseling, and public campaigns). Despite these initiatives, several challenges persist. Limited public awareness, inadequate infrastructure and facilities, a shortage of skilled human resources, weak planning and socialization, complex disaster causes, and environmental vulnerabilities all reduce the overall effectiveness of disaster risk reduction efforts. To address these obstacles, BPBD Manado fosters collaboration with various stakeholders, including government institutions, academia, non-governmental organizations, and local community groups. Moreover, the agency emphasizes the use of disaster risk assessments and hazard mapping as evidence-based foundations for policy formulation and implementation.